Respon Tanaman Bawang Merah (Allium ascolonicum L. ) Varietas Tuk Tuk Terhadap Pengaturan Jarak Tanam dan Konsentrasi Pupuk Organik Cair Nasa - Tutik Nugrahini (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2013)
The research objectives are to: (1) study the response of the red onion upon the plant spacing and application of Nasa liquid organic fertilizer (POC) concentrations and their interactions, and (2) to obtain the proper plant spacing and Nasa POC concentration for red onion crop.  The study was conducted from May to September 2011 start of preparation, data collection, analysis and report writing.  Research site is in the South Sempaja Urban village, Sub district of North Samarinda, Samarinda.   Completely Randomized Block Design was applied for this study, using 4 x 4 factorial pattern with 3 replications.  The first factor was the plant spacing (J) consists of: 10cm x 15cm (j1), 15cm x 15cm (j2), 15cm x 20cm (j3), and 20cm x 20cm (j4).  The second factor was the Nasa POC (P) consists of: no POC Nasa application or 0 ml l-1 water (p0) , 1 ml l-1 water (p1), 2 ml l-1 water (p2), and 3 ml l-1 water 1 (p3).  Analysis of the data using analysis of variance, when the results were significantly different (F count > F table 5%) or very significant (F count > F table 1%), then to compare the two treatments used the least significant difference test at level of 5%.  The results showed that: (1) the responses of plant height at age 20 and 60 days after planting, the number of leaves at age of 40 and 60 days after planting, and tuber production are significantly different to highly significant upon the plant spacing.  The highest tuber production was attained at plant spacing of 10cm x 15cm (j1), with 11.72 Mg ha-1; (2) responses of plant height at age 20, 40 and 60 days after planting, the number of leaves at age 20, 40 and 60 days after planting, the number of tillers at the age of 40 and 60 days after planting, tuber weight per plot, and the production of tubers are significantly different upon the Nasa POC concentration.  The highest tuber production was attained at Nasa POC treatment with concentrations of 3 ml l-1 water (k4), with 9.12 Mg ha-1, and (3) there is no interaction between the plant spacing and Nasa POC concentration on all parameters observed.